ASSOCIATION OF ABO AND RH BLOOD GROUP WITH COVID-19 INFECTION IN PAKISTAN - Rasheed, Seher; Moiz, Bushra (Infectious Diseases Journal of Pakistan, 2022)
Background: The role of various blood groups with COVID-19 has recently been observed. Individuals with blood group O are supposedly less susceptible when compared to those with non- O blood group. This study aimed in observing the association of ABO and Rh (D) blood groups in patients having COVID-19 in the local setting. Material and Methods: In this retrospective study, 1238 patients admitted in the hospital with COVID-19 during 2020 and 2021 were studied for their demographics and blood groups. Healthy blood donors were enrolled and served as a control group. Chi-square was used to determine the association (odd ratio) of various blood groups with COVID-19. Results: Blood group B was predominant (39% vs 33%) while O was less common (31% vs. 36%) in admitted patients having COVID -19 compared to blood donors. The study showed a negative association of blood group O among patients with COVID-19 (OR 0.783; 95%CI 0.677-0.906, p-value 0.001) while a positive association with blood group B (OR 1.266, 95%CI 1.099-1.458, p-value 0.001). No association was seen with blood groups A, AB and Rh. Conclusion: The small scale and a single centre study showed a preponderance of blood group B while a low frequency of blood group O in patients admitted with COVID-19. This may reflect the protective nature of blood group O for COVID-19 infection. Large scale studies are needed to further understand this association. Keywords: Blood group, COVID-19, Pakistan